Hubungan Pengetahuan Lansia Tentang Senam Lansia dengan Praktik Senam Lansia di Posyandu Lansia - Aprilia Nurtika Sari (Jurnal Sehat Mandiri, 2020)
Among the vulnerable population are the elderly. One of the physical activities recommended for the elderly is elderly exercise. This study aims to identify the correlation between the knowledge of the elderly about elderly exercise with the practice of elderly exercise in the Elderly Posyandu in Kepuh Village, Kertosono District, Nganjuk Regency. The research design used was analytic with a cross sectional approach. The population in this study were all elderly registered in the Elderly Posyandu in Kepuh Village, Kertosono District, Nganjuk Regency, totaling 30 people. The sample consisted of 30 people who were determined by total sampling technique. To analyze the correlation, the Spearman Rho test was used. The results obtained from 30 respondents, there were 13 respondents (43.33%) who had sufficient knowledge and did not routinely do elderly exercise, 12 respondents (40%) had good knowledge and routinely did elderly exercise. There is a correlation between knowledge about elderly exercise and the practice of elderly exercise. The better the knowledge of the elderly about elderly exercise, the more routine they will participate in elderly exercise. These results indicate that knowledge has an important role to play in increasing motivation and shaping one's health behavior. Therefore, health workers are expected to be active in providing health information through counseling at the elderly posyandu and other community activities.